Implementation of a One-LLID-per-Queue DBA algorithm in EPON - Radzi N.A.M.; Din N.M.; Al-Mansoori M.H.; Zainol Abidin H. (Hindawi Publishing Corporation, 2023)
The advantages of Ethernet passive optical network (EPON) are setting it to be a natural ubiquitous solution for the access network. In the upstream direction of EPON, the directional property of the splitter requires that the traffic flow be mitigated to avoid collision. A dynamic bandwidth allocation (DBA) scheme is desirable in optimizing the bandwidth usage further. In this paper, a global priority DBA mechanism is discussed. The mechanism aims to reduce the overall delay while enhancing the throughput and fairness. This study was conducted using MATLAB where it was compared to two other algorithms in the literature. The results show that the delay is reduced up to 59% and the throughput and fairness index are improved up to 10% and 6%, respectively. © 2014 N. A. M. Radzi et al.